2017
DOI: 10.1111/1468-0106.12217
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Production Structures and Efficiency: An Analysis of the Czech Food Processing Industry

Abstract: The present study analyses firm heterogeneity and sector‐specific technology. The theoretical model stands on the assumption of maximizing the return on capital and overcomes problems involved in simple profit maximization. The results show that a random parameter model with sector dummies and heteroscedasticity is the most appropriate model specification for distinguishing firm‐level and sector‐level efficiency and heterogeneity. The heterogeneity among firms as well as among sectors was found to be an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…High technical efficiency of the top 10% of food processors is a common feature for all countries in all analysed sectors. Similar findings were provided for Czechia byČechura and Hockmann [8] and Špička [11]. On the other hand, lower technical efficiency scores were estimated for the Czech food processing industry by Náglová and Šimpachová Petrová [7].…”
Section: Discussionsupporting
confidence: 77%
“…High technical efficiency of the top 10% of food processors is a common feature for all countries in all analysed sectors. Similar findings were provided for Czechia byČechura and Hockmann [8] and Špička [11]. On the other hand, lower technical efficiency scores were estimated for the Czech food processing industry by Náglová and Šimpachová Petrová [7].…”
Section: Discussionsupporting
confidence: 77%
“…According to Karagiannis et al [58], any IDF is concave in inputs and quasiconcave in outputs if the Hessian matrix of the second-order IDF's parameter derivative is negative-definite with respect to outputs and positive-definite with respect to inputs, at the point of approximation. AsČechura and Hockmann [59] noted, this is fulfilled on the sample mean if β jj + β j 2 − β j ≤ 0 for all j. Since all these conditions are met, the estimated input-distance functions seem to well approximate the production behaviour of farmers in selected European countries.…”
Section: Milk Production Technologymentioning
confidence: 72%
“…Those classified as current assets include cash and cash equivalents, receivables, short-term investments, inventory, and prepaid expenses. Previous research results showed that higher current assets owned by the company impact the level of technical efficiency of the company, which can be seen from the t-ratio: if it is higher than the p-value (5%), it means the current asset gives significant effect through firm efficiency [10,12,28,38,39,41,42].…”
Section: Current Assetsmentioning
confidence: 97%
“…In the measurement of TE, there are provisions for the input-output selection approach. This study uses a production approach, referring to the research of [38][39][40][41][42]. The selection of input variable in this study includes current assets, fixed assets, liabilities, and capital.…”
Section: Technical Efficiencymentioning
confidence: 99%
See 1 more Smart Citation